Border identities in Ana Rossetti and Almudena Grandes. Towards an overcoming of the category of 'queer' (Anclajes, 2017)
Ana Rossetti’s Los devaneos de Erato (1980) and Almudena Grandes’ Las edades de Lulú (1989) are literary texts that challenge the bourgeois, heterosexual and catholic order by presenting models of femininity whose voice and body avoid the cultural and naturalized definitions of the female gender. The purpose of this article is to consider the characteristics of what we describe as border identities by means of literary analysis and the contributions of Gender Studies. We lay aside the use of the category of queer, which on occasion may seem a useful tool for the analysis of these texts. Instead, we promote descriptions that underscore the singularity of the Spanish historic, cultural, and social context, with which these identities and voices are confronted.
Keywords: Ana Rossetti; Almudena Grandes; Spanish Contemporary Literature; Gender Studies; Spain